Carcinoma gástrico de células en anillo de sello en un perro : reporte de un caso (2004)
ABSTRACT: In the present work we report a case of a keeshound dog suffering from progressive chronic vomiting. At clinical examination the dog was caquectic and no other clinical finding were noticed. Hematological and biochemical analysis were normal and an abdominal radiographic survey didn’t find abnormalities. A gastroscopy was performance revealing an increased mucosal surface surrounding an ulcerated area in the greater curvature. Histopathological analysis of biopsies taken during the procedure revealed the presence of a signet ring cell gastric carcinoma, considered the first case diagnosed by an endoscopic procedure in Medellin. An exploratory laparotomy was practiced in order to consider a possible surgical approach, but because of the high level of metastases founded, the dog was euthanised. Histological examination revealed metastasic transformation of mesenteric lymph nodes, epyplon and spleen. Instead of being considered as a rare clinical entity in dogs, gastric neoplasia must be considered in dogs affected by progressive chronic vomiting, practicing an endoscopic examination of the gastric mucosa and sampling biopsies specimens from reliable areas for histopathological evaluation.